How historical and present climat conditions affected the distribution of the mediterranean whter shrew?:a phylogeographical and ecological approach - Tapisso, Joaquim (2014)
Tese de doutoramento, Biologia (Biologia Evolutiva), Universidade de Lisboa, Faculdade de Ciências, 2014